2010
DOI: 10.1016/j.nmd.2010.07.276
|View full text |Cite
|
Sign up to set email alerts
|

Personalized exon skipping strategies to address clustered non-deletion dystrophin mutations

Abstract: Antisense oligomer induced exon skipping is showing promise as a therapy to reduce the severity of Duchenne Muscular Dystrophy. To date, the focus has been on excluding single exons flanking frame-shifting deletions in the dystrophin gene, however, a third of all Duchenne Muscular Dystrophy causing mutations are more subtle DNA changes. Forty-five dystrophin exons are potentially frame-shifting and mutations in these will require the targeted removal of exon blocks to generate in-frame transcripts. We report t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…This was not unexpected, as we have previously showed that small DMD mutations can influence oligomer‐mediated exon skipping outcomes (Forrest et al. ; Fragall et al. ).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This was not unexpected, as we have previously showed that small DMD mutations can influence oligomer‐mediated exon skipping outcomes (Forrest et al. ; Fragall et al. ).…”
Section: Discussionsupporting
confidence: 61%
“…As we have found with other small dystrophin gene lesions, it appears that the various dystrophin splice site mutations will require personalized oligomer design and exon skipping strategies on a case‐by‐case basis (Forrest et al. ; Fragall et al. ; Adkin et al.…”
Section: Introductionmentioning
confidence: 85%
“…Skipping of an additional exon could restore the reading frame again. For example for an exon 18 duplication, successful skipping of exon 17 and both exon 18s resulted in restoration of the reading frame (Forrest et al, 2010). Successful skipping of multiple exon duplications has not yet been achieved .…”
Section: Double and Multiple Exon Skippingmentioning
confidence: 99%
“…Specific destruction of mRNA species can also be used for applications such as antiviral therapy. Another developing strategy involves RNA editing, with an exciting example being synthetic oligonucleotide‐induced exon skipping, 17 which is being trialed for Duchenne muscular dystrophy 18 …”
Section: Simple In Theory Complex In Practicementioning
confidence: 99%